Pengaruh Penambahan Karboksil Metil Selullosa (CMC) Terhadap Karakteristik Kimia dan Organoleptik Sirup Jeruk Kisar - Augustyn, Gelora H (Jurnal Agrosilvopasture-Tech, 2024)
This research aims to determine the effect of adding Carboxyl Methyl Cellulose (CMC) on the chemical and organoleptic characteristics of kisar lemon syrup. The design used was a single factor Completely Randomized Design with 4 treatment levels and 3 replications. The treatment levels in this study were P1 (no CMC), P2 (CMC 0.5%), P3 (CMC 1%), P4 (CMC 1.5%). Observations were made on total acid, vitamin C, total sugar, water content and pH, while organoleptic tests were on color and level of preference. The results showed that the highest total acid and water content of kisar orange syrup was found in treatment P1 (CMC 0%) respectively 2.74%, 77.9%, while the highest Vitamin C, total sugar and pH were found in treatment P4 (CMC 1.5%) respectively 0.021%, 22.81% and 5.37.